2011
DOI: 10.1271/bbb.100880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnesium Sulfate on the Luminescence ofVibrio fischeriunder Nutrient-Starved Conditions

Abstract: In this study, we investigated the relationship between MgSO(4) and luminescence in Vibrio fischeri under nutrient-starved conditions. When V. fischeri was cultured in an artificial seawater medium, the luminescence intensity was low relative to that observed under normal growth conditions. It decreased during the initial 14 h, and then increased slightly at 24 h. This regulation of luminescence was not dependent on the quorum-sensing mechanism, because the cell densities had not reached a critical threshold c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
1
12
0
3
Order By: Relevance
“…Some studies have shown that cell density‐independent luminescence can be regulated by various factors, such as heat shock proteins , UV irradiation , osmolarity , and redox state . In addition, we recently demonstrated the induction of cell density‐independent luminescence in V. fischeri by the addition of sulfur compounds , which was enhanced by the addition of potassium, bicarbonate, and magnesium . Similarly, in the present study, cell density‐independent luminescence of P. luminescens was induced by the addition of potassium, bicarbonate, and magnesium (Figs.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Some studies have shown that cell density‐independent luminescence can be regulated by various factors, such as heat shock proteins , UV irradiation , osmolarity , and redox state . In addition, we recently demonstrated the induction of cell density‐independent luminescence in V. fischeri by the addition of sulfur compounds , which was enhanced by the addition of potassium, bicarbonate, and magnesium . Similarly, in the present study, cell density‐independent luminescence of P. luminescens was induced by the addition of potassium, bicarbonate, and magnesium (Figs.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to these autoinducer‐mediated regulatory mechanisms, we recently demonstrated that the regulation of V. fischeri luminescence in artificial seawater containing NaCl, KCl, MgCl 2 , CaCl 2 , NaHCO 3 , and MgSO 4 was independent of cell density . Moreover, we showed that induction of this type of luminescence required the addition of sulfur‐containing compounds, including sulfate and L‐cysteine , which was enhanced by the addition of potassium, bicarbonate, and magnesium .…”
Section: Introductionmentioning
confidence: 96%
“…V. fischeri (ATCC 49387) was obtained from the American Type Culture Collection and grown in 100 ml of nutrient broth (NB) (Becton, Dickinson) supplemented with 3% NaCl in 300 ml flasks, which were agitated on a shaker at 70 rpm at 22 °C. V. fischeri was also cultured at 22 °C in artificial seawater (ASW) [16,17], which was composed of 28.1 g/l of NaCl, 0.77 g/l of KCl, 1.21 g/l of CaCl 2 , 4.8 g/l of MgCl 2 ⋅ 6 H 2 O, 0.11 g/l of NaHCO 3 , and 3.5 g/l of MgSO 4 ⋅ 7 H 2 O. Bacterial proliferation was monitored by measuring the increase in optical density of the culture suspension at 600 nm (OD 600 ).…”
Section: Methodsmentioning
confidence: 99%
“…In V. fischeri, these autoinducers are N-3-oxo-hexanoyl homoserine lactone (3-oxo-C6-HSL), N-octanoyl homoserine lactone (C8-HSL), and presumably a furanosyl borate diester, which are produced by LuxI, AinS, and LuxS, respectively, and collectively stimulate the transcription of a set of luminescent genes, luxICDABEG [2, 6 -10].In contrast to cell density-dependent luminescence, some studies have shown that cell density-independent luminescence can be regulated by various factors, such as heat shock proteins [11,12], UV irradiation [13], osmolarity [14], and redox state [15]. In addition, we recently discovered cell density-independent luminescence induced under nutrient-starved conditions [16]. Moreover, we demonstrated that this type of luminescence required the addition of sulfur compounds [16,…”
mentioning
confidence: 99%
“…Among the factors that influence the growth and luminescence of A. fischeri are the medium composition, pH (optimum range between 6.0 and 9.0), temperature (optimum range between 25°C and 30°C) and NaCl (optimum range between 1.75–4%) . These culture media frequently used to grow A. fischeri include seawater complete medium (SWC), which is prepared with artificial seawater (ASW), Photobacterium broth; and high‐salt Luria–Bertani medium (LB) . Other formulations used to grow A. fischeri are composed of yeast extract, tryptone, peptone, sodium chloride, glycerol, magnesium chloride, magnesium sulfate, calcium chloride, and sodium phosphates .…”
Section: Introductionmentioning
confidence: 99%